White Masculinity in the Recent South - Brown, Trent, 1965- (Book collections on Project MUSE., 2008)
From antebellum readers avidly consuming stories featuring white southern men as benevolent patriarchs, hell-raising frontiersmen, and callous plantation owners, to postCivil War southern writers seeking to advance a model of southern manhood and male authority as honorable, dignified, and admirable, the idea of a distinctly southern masculinity has reflected the broad regional differences between North and South. In WHITE MASCULINITY IN THE RECENT SOUTH thirteen scholars of history, literature, film, and environmental studies examine modern white masculinity, including such stereotypes as the.